The diagnostic assessment strategy in the Merdeka Curriculum for Indonesian language learning in 7th grade at Junior High School - refoina, rindu; Rustam (Institut Agama Islam Negeri Palopo, 2024)
This research aims to evaluate diagnostic assessment strategies that are effective in improving understanding of Indonesian language material in junior high school students. Diagnostic assessments are used as a tool to identify specific difficulties experienced by students in understanding the material contained in Indonesian language learning. In each cycle, diagnostic assessments are carried out through written tests and interviews, the results of which are analyzed to design appropriate learning interventions. The research results show that the application of diagnostic assessment strategies significantly increases students' ability to understand the material. In addition, students show an increase in motivation and interest in learning Indonesian. These findings indicate that diagnostic assessments are not only useful in identifying learning difficulties, but also effective in designing learning strategies that are adaptive and responsive to student needs.